A response spectrum-based indicator for structural damage prediction. (1st July 2018) - Deng, Peng; Pei, Shiling; Hartzell, Stephen; Luco, Nicolas; Rezaeian, Sanaz
Abstract: Improving predictive relationships between strong ground motion and seismically induced damage in buildings is an important topic for seismic risk assessment. Spectral acceleration at a structure's fundamental period S a ( T 1 ) has often been used as the indicator of the potential damage a given ground motion may induce on structural systems. However, such a scalar indicator (Damage Potential Indicator, DPI) captures only limited information about the ground motion time history and response spectrum shape. In a severely damaged state, the effective period of a structure will change, which makes the structure respond to other parts of the response spectrum. In this study, a new response spectrum-based DPI that contains an intensity component and a spectral shape component is proposed. The critical period range of the response spectrum that should be considered in spectral shape evaluation is determined using a circle rule for bilinear single-degree-of-freedom (SDOF) systems. The effectiveness of the newly proposed DPI is validated by comparing damage potential similarity using a database of ground motion records.